2017
DOI: 10.1038/s41598-017-13110-y
|View full text |Cite
|
Sign up to set email alerts
|

Zebra Finch chicks recognise parental scent, and retain chemosensory knowledge of their genetic mother, even after egg cross-fostering

Abstract: Mechanisms underlying parent-offspring recognition in birds have fascinated researchers for centuries. Yet, the possibility that chicks recognise parental odour at hatching has been completely overlooked, despite the fact that olfaction is one of the first sensory modalities to develop, and social chemosignals occur in avian taxa. Here we show that Zebra Finch chicks (Taeniopygia guttata) are capable of identifying parental odours at hatching. In our first experiment, chicks begged significantly longer in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 57 publications
(72 reference statements)
2
41
0
Order By: Relevance
“…For the nest scent recognition experiment, we tested nestlings at 1 day of age and found no difference in response between orange scent and water, whereas for the parent scent recognition experiment, we tested nestlings at 2 days of age and found a change in response depending on the scent type. Similar experiments on zebra finches performed on the day of hatch (Caspers et al, ) or 1 day after hatch (Caspers et al, ) found significant effects in response to odour type, while an experiment on blue tits, which also found significant effects in response to odour type, tested nestlings at 7 days post‐hatch (Rossi et al, ). As our experiment was the first such experiment on tree swallows, however, we cannot rule out that olfactory development may be slower in nestling tree swallows than zebra finches, and therefore, they may be more responsive to odour stimuli when they are older.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…For the nest scent recognition experiment, we tested nestlings at 1 day of age and found no difference in response between orange scent and water, whereas for the parent scent recognition experiment, we tested nestlings at 2 days of age and found a change in response depending on the scent type. Similar experiments on zebra finches performed on the day of hatch (Caspers et al, ) or 1 day after hatch (Caspers et al, ) found significant effects in response to odour type, while an experiment on blue tits, which also found significant effects in response to odour type, tested nestlings at 7 days post‐hatch (Rossi et al, ). As our experiment was the first such experiment on tree swallows, however, we cannot rule out that olfactory development may be slower in nestling tree swallows than zebra finches, and therefore, they may be more responsive to odour stimuli when they are older.…”
Section: Discussionmentioning
confidence: 78%
“…Second, odour recognition of parents may be an innate character, and cross‐fostering would be necessary to test this. In zebra finches, such an experiment showed that nestlings preferred the odour of their genetic, rather than foster, mother, but showed no preference between genetic and foster fathers (Caspers et al, ). In tree swallows, however, most broods contain extra‐pair young (O'Brien & Dawson, and references therein), so some nestlings may be genetically unrelated to the male that provides care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Olfactory information for songbirds is most likely carried in uropygial gland oils, which have been shown to possess species-specific chemical compositions (Soini, Whittaker, Wiesler, Ketterson, & Novotny, 2013). Recent work suggests a role for olfaction in many aspects of avian ecology (reviewed in Caro & Balthazart, 2012) including species discrimination (Bonnadonna & Mardon, 2010;Whittaker et al, 2011;Zhang, Du, & Zhang, 2013), sex discrimination (Amo et al, 2012;Soini et al, 2007;Whittaker et al, 2010;Zhang, Sun, & Zuo, 2009;Zhang, Wei, Zhang, & Yang, 2010), threat detection (Amo, Galván, Tomás, & Sanz, 2008;Amo, Visser, & Oers, 2011;Roth, Cox, & Lima, 2008), individual quality (Amo et al, 2012;Whittaker, Gerlach, Soini, Novotny, & Ketterson, 2013), aggression (Whittaker et al, 2018), nest recognition (Caspers, Hoffman, Kohlmeier, Krüger, & Krause, 2013;Golüke, Dörrenberg, Krause, & Caspers, 2016), and kin recognition (Bonadonna & Sanz-Aguilar, 2012;Caspers, Gagliardo, & Krause, 2015;Caspers et al, 2017;Coffin, Watters, & Mateo, 2011;Krause, Kruger, Kohlmeier, & Caspers, 2012). Still, whether conspecific preferences for divergent odor cues exist in natural songbird hybrid zones and therefore whether odor cues might function as a premating barrier in songbirds remain unknown (Campagna, Mardon, Celerier, & Bonadonna, 2011;Caro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%